Pediatric dental care focused on trauma in children's dentition (Research, Society and Development, 2022)
Dental trauma is a very common situation in children and adolescents. These injuries can range from simple enamel fractures to the permanent loss of the tooth element, predominantly in males, commonly at school, as a result of falls, fights or fights, sports, car accidents, trauma to objects and abuse. Traumas in primary dentition occur in preschool age, usually linked to behavioral characteristics, such as curiosity and restlessness, which lead the child to explore environments, causing falls and, consequently, the occurrence of injuries becomes high. This work consists of a literature review, in which a selection of articles on pediatric dental care focused on trauma in children's teeth was carried out. The databases used to prepare this review are found in the electronic libraries: MedLine, Lilacs and Scielo. As a search strategy, we use the following keywords: dental trauma, pediatric dentistry, accident prevention. Trauma in primary dentition has some consequences for the oral cavity, which can lead to a change in the dental position in the arch, consequently modifying its alveoli, there can also be a change in the color of the teeth, which are generally more darkened or yellowish. highlighting the other dental elements of the cavity, in addition to dental mobility, painful symptoms due to injuries to the ligaments, mucosa, gums and even bone level, promoting sensitivity, which may or may not present long-term root or bone resorption or ankylosis, necrosis and loss of the dental element, either at the time of trauma or later due to the level of injury or fracture. Through the correct diagnosis, it is possible to identify the origin of the trauma, mapping the injury, as well as its implications for the health and life of the child patient, enabling a resolute planning in order to keep the dental element in the oral cavity when possible, thus avoiding invasive interventions and favoring the patient's functional and emotional recovery. Full knowledge on the part of professionals about the signs and management of violence, maltreatment and abuse against children must always exist, as having this perception of changes in their behavior linked to the characteristics of their possible injuries, it is possible to identify more agile and carry out the appropriate intervention through contact with the Guardianship Council.